Anticholinergic Burden: A Bibliometric Analysis of Research Trends - Sümbül-Şekerci, Betül; Pasin, Özge; Velioğlu, Halil Aziz (Trends in Pharmacy, 2025)
Background: Anticholinergic burden is linked to adverse outcomes, including mortality, cardiovascular events, falls, cognitive decline, and dementia, particularly in middle- to older-aged populations. This study aims to provide a comprehensive quantitative analysis of the research landscape surrounding anticholinergic burden using bibliometric methods. Methods: We searched the last 40 years of databases on the Web of Science platform using various keywords related to anticholinergic burden. Bibliometric analysis and mapping were carried out using VOSviewer software, and the most prominent research, countries, institutions, authors, journals, co-citations, and keywords were revealed. Results: A total of 1239 documents published between 1984 and 2024 were identified, with 2020 having the highest number of publications. Seventy-five countries contributed to studies on anticholinergic burden, with the United States leading with 382 publications and 12 023 citations. “Polypharmacy” was the most frequently used keyword in these articles. Over the last 40 years, the most productive author in this field was Sarah H. Hilmer, with 77 publications and 3255 citations. Conclusion: This study offers researchers a comprehensive summary and analysis of the research on anticholinergic burden. Anticholinergic burden, a multidisciplinary research focus, continues to attract worldwide interest. The cumulative impact of polypharmacy on anticholinergic burden remains a key area of clinical research. Although numerous scales have been developed to assess anticholinergic burden, there remains a significant need for more accurate methods that account for drug dosages, potencies, and individual predispositions, as there is a lack of strong agreement among existing scales. Cite this article as: Sümbül-Şekerci, B., Pasin, Ö., & Velioğlu, HA. Anticholinergic burden: a bibliometric analysis of research trends. Trends Pharm, 2025, 2, 0004, doi: 10.5152/TrendsPharm.2025.24004.